Gastrointestinal stromal tumor: Computed tomographic features - Lee, Chi-Ming (World J Gastroenterol, 2004)
AIM: Gastrointestinal stromal tumor (GIST) is a rare type of cancer. Computed tomography (CT) is an imaging modality of choice for diagnosing GIST. The aim of this retrospective study was to review the CT imaging features of 17 GIST patients. METHODS: From 1995 to 2003, there were 47 patients with pathologically proven GISTs at our hospital. Of these, 17 patients underwent preoperative CT. We collected and analyzed these CT images. The CT imaging features included tumor diameter, number and location, tumor margin, location of metastasis, hounsfield units of tumor and effect of contrasts. In addition, we also recorded the surgical findings, including complications, tumor size and location for comparative analysis. RESULTS: The results showed that 12 (70%) tumors were located in the stomach and five (30%) were located in the jejunum mesentery. GISTs were extraluminal in 12 (70%) patients. The tumor margins of 13 (76%) tumors were well defined and irregular in four (24%). The effect of contrast enhancement on GIST CT imaging was homogenous enhancement in 13 (76%) and heterogeneous enhancement in four (24%). The hounsfield units (HU) were 30.41 ± 5.01 for precontrast images and postcontrast hounsfield units were 51.80 ± 9.24. CONCLUSION: The stomach was the commonest site of GIST occurrence among our patients. The CT features of GIST were well-defined tumor margins, homogenous enhancement on postcontrast CT images.